PARENTS IN PAIN: Overcoming the Hurt & Frustration of Problem Children - JOHN WHITE (United States of America INTERVARSITY PRESS DOWNER GROVE, ILLINOIS 60515, 1979)
A police car rolls up in front of your house--with your son in the back seat. A voice on the phone says your daughter is all right but won't tell you where she is--and then hangs up. A wallet disappears from your dresser and you're sure who took it--at least, somewhat sure. Many parents face problems beyond their ability to cope. John White ofers comfort to parents of children with severe problems--alcoholism, homosexuality, even suicide. Though he gives practical suggestions, this is not a how-to manual for making rebellious children behave. Rather the author helps all parents deal with their own guilt, frustration, anger and sense of inadequacy. White first asks, Why has the child rearing become such a complicated task? He looks to common sense, science and the Bible for an answer. Next he focuses on the parent-child relationship itself as trust erodes, arguments arise and the need for professional or legal counsel develops. Finally, he cautions us to avoid parenting techniques which emphasize pragmatism at the expense of what is moral and just. A book of comfort and counsel to parents in pain.